Peran Rembuk Stunting Dalam Mewujudkan Anak Sehat Di Desa Teluk Pambang - Samsir Samsir; Syahdatul Nisa; Nabilah Ulfah; Miskia Afdita Januarahmi; Khoirul Liyana; Putri Nor Afiza; Normalina Normalina; Ici Fatria Zarni; Jupri Dwi Kurniawan; Irud Dirmansyah; Apta Priatama (FKIP, Universitas Palangka Raya, 2023)
The problem of stunting is still a serious challenge in various regions in Indonesia, including in Teluk Pambang Village, which is a coastal and outermost area. Stunting is a condition of lack of optimal growth in children due to malnutrition and other risk factors, with long-term impacts that have the potential to hamper children's physical, cognitive and social development. Rembuk stunting is an effective method of involving various stakeholders, such as local communities, nutritionists, health workers, and other related parties. This activity aims to identify and address stunting problems and find alternative solutions to prevent stunting in Teluk Pambang Village. The community service program used a qualitative approach. The work procedure approach in this activity includes needs identification, team selection, focused discussions, situation analysis and strategy selection and evaluation. The results obtained found that this stunting meeting was effective in increasing community awareness, participation, and cooperation in stunting prevention efforts.